P0808DEFINING CRITERIA FOR CKD STAGE 3 PATIENTS NEPHROLOGY REFERRAL: AN ANALYSIS FOCUSED ON CKD PROGRESSION AND MORTALITY RISK. (6th June 2020) - Falcao, Luis; Fernandes, Sara; Fernandes, Adriana Paixão; Donato, Beatriz; Raimundo, Mário; Teixeira, Catarina; Costa, Ana Cortesão; Silva, Sónia; Macedo, Ana; Almeida, Edgar
Abstract: Background and Aims: The high prevalence of CKD and its increasing awareness by primary care clinicians is posing a huge burden over health care systems, especially over Nephrology departments. While the referral of CKD stage 4 and 5 to a nephrology clinic is undisputable, the need for stage 3 patients referral is still subject to debate. Our objective was to investigate baseline characteristics of CKD stage 3 patients associated with subsequent CKD progression, in order to help determine which patients should be referred at this stage. Additionally, we investigated the association of CKD stage 3 progression with morbidity and overall mortality. Method: We conducted a patient-level, retrospective, cohort analysis of all patients referred to a nephrology clinic over a 6 years period. We included CKD stage 3 patients with at least 36 months of follow-up or 24 to 36 months of follow up with more than 3 serum creatinine determinations. CKD progression was defined by one of the following: 1) an eGFR (CKD-EPI) decline superior to 5mL/min/year; 2) Serum creatinine duplication; 3) The need for chronic RRT. Baseline covariates included demographics, comorbid conditions and laboratory values. Univariate and multivariate analysis were employed to determine independent predictors of CKD progression and mortality. Results: Out of the 3008 patients referred to the nephrology clinic, 1288 (42.8%) were CKD stage 3 patients and from these, 594 (19.8%) met the inclusion criteria (median age: 71.9 years; 63.8% male). Median follow-up was 4.9 years (IQR 2.2). 133 (22.4%) met the criteria for CKD progression and 110 (18.6%) died. In univariate analysis, CKD progression was associated with higher proteinuria (405.7 vs 65.5mg/gr, p<0.001), Diabetes (60.9 vs 45.3%, p=0.002), Congestive heart failure (CHF) (40.6 vs 28.7%, p=0.009), Anemia (OMS definition) (68.0 vs 44.7%, p<0.001), higher diuretic use (48.9 vs 34.1%, p=0.002) and higher mortality (40.9 vs 12.2%, p<0.001) In multivariate logistic regression analysis, albuminuria over 300 mg/gr [Odds ratio (OR) 3.57, 95% CI 2.20 - 5.80, p<0.001] and Anemia (OR 1.97, 95% CI 1.20 – 3.22, p=0.007) were associated with CKD progression. The possible association with other variables was not confirmed. The independent predictors of mortality were: CKD progression (OR 4.49, 95% CI 2.69-7.50, p=<0.001), Older age (OR per 1 year increase 1.03, 95% CI 1.01-1.05, p=0.003), presence of CHF (OR 1.75, 95% CI 1.03-2.98, p=<0.037), presence of Hyperkalemia at first consultation (OR 2.12, 95% CI 1.00 – 4.52, p=0.049) and Anemia (OR 1.93, 95% CI 1.03 - 3.62, p=0.025). Higher body mass index was associated with a lower risk of mortality (OR 0.58, 95% CI 0.35 – 0.95, p=0.033) Conclusion: Our study suggests that patients with macroalbuminuria and anemia at first consultation are at increased risk for rapid CKD stage 3 progression. In this group, patients with CHF, anemia and hyperkalemia (even at first consultation) have a higher risk of mortality. This study may be useful and help us in guiding which CKD stage 3 patients should be referred to a nephrology clinic.